Attitudes toward English phonetics learning: a survey on Indonesian EFL learners - Sri Ayu Istiqomah; Alies Poetri Lintangsari; Widya Caterine Perdhani (Journal on English as a Foreign Language, 2021)
Indonesian EFL learners face challenges in comprehending English phonemes as it becomes one of the significant predictors of English literacy. Hence, the English Phonetics subject is considered one of the most difficult ones, making the teaching and learning process less effective. Addressing Indonesian EFL learners’ attitudes toward English phonetics teaching is significant to improve phonetics teaching, yet, research on this has not received much attention. This present study was conducted to explore EFL learners’ attitudes toward English phonetic learning. A quantitative approach with survey design was employed involving 112 Indonesian EFL students. The researchers identified students’ attitudes using an adapted questionnaire from Lintunen and Mäkilähde (2015). Statistical Package for the Social Sciences (SPSS) version 25 was utilized to analyze the data. The results indicate that Indonesian EFL students perform positive attitudes toward English phonetic learning, although they confess that phonetics is challenging. It implies that phonetics learning is potential and promising to support their English fluency; hence, lecturers need to make phonetics Learning more enjoyable, easier and participating in drawing the students' full engagement by considering their preferences and attitude toward phonetics learning.